PTU-070 The fate of epithelial keratins in recent-onset and long-standing colitis in remission. (22nd June 2015) - Assad-Sangabi, A; Evans, C; Majumdar, D; Cross, SS; Corfe, BM; Lobo, AJ
Abstract : Introduction: Intermediate filaments (IF), which mainly consist of keratins (K), are one of the main components of the human cell cytoskeleton. K8, K18 and K19 constitute the main keratins in the intestinal epithelial cells. We have previously shown increased expression of epithelial keratins in the IF fraction from long-standing UC (>20 years) in remission (LSPC) relative to recent –onset ulcerative colitis (≤5 years) in remission (ROUC) using proteomic iTRAQ-based analysis. 1 Whether this reduced expression is due to change in solubilisation or reduced total expression is unknown. We aimed to clarify the fate of epithelial keratins during UC disease evolution in the two cohorts. Method: Soluble proteomes were extracted from individual biopsies in patients with LSPC in clinical, endoscopic and histological remission (n = 10) and ROUC in remission (n = 8). Median interval from last relapse to the index endoscopy in LSPC and ROUC was 31 and 1 month, respectively. Median histological activity index in both groups were 0 (range 0–1). An iTRAQ-compatible extraction protocol for soluble proteins was applied. Inter-group comparisons were made using in-house algorithms based on t-testing with multiple test correction. Validation of iTRAQ results was carried out with immunoblotting on pooled and individual samples using monoclonal antibody against K8. These outcomes were then compared with our previous insoluble proteome analyses. 1 Results: Comparative iTRAQ analysis of the soluble fraction showed no statistically significant log fold changes in K8, K18 and K19 levels in LSPC relative to ROUC and normal controls. Median relative K8 concentration in IF/soluble proteome fraction in individual LSPC and ROUC samples were 1.54/10.34 and 0.03/10.93, respectively. Relative K8 concentration was significantly higher in LSPC relative to ROUC in the IF fraction (p = 0.001), whereas the same comparison did not reach statistical significance for the soluble fraction (p = 0.82). Conclusion: This study suggests relative total increase in expression of epithelial keratins in colonic epithelial cells during LSPC compared to the levels in ROUC. Comparing K8 IF and soluble bands in ROUC showes change in solubilisation relative to control, which in turn suggest effect of recent inflammation on increased keratin solubility in this group. Whether restoration of K8 is a marker of deep remission beyond histological and endoscopic remission needs to be further investigated. Disclosure of interest: None Declared. Reference: Corfe BM, Majumdar D, Assadsangabi A, Marsh AMR, Cross SS, Connolly JB, Evans CA, Lobo AJ. Inflammation decreases keratin level in ulcerative colitis; inadequate restoration associates with increased risk of colitis-associated-cancer. BMJ Open Gastroenterol ., In press